The Multifaceted Role of Extrachromosomal DNA in Cancer: Functions and Clinical Implications - Ur Rehman, Shafee (Bangladesh Journal of Medicine, 2025)
The Extrachromosomal DNA (ecDNA) in cancer biology has emerged as a critical driver, enhancing the knowledge about tumorigenesis, progression and treatment. The current review article explores the multifaceted role of Extrachromosomal DNA, focusing on its ability to amplify oncogenes, enhance tumor heterogenicity, and support cancer cell survival and understanding therapeutics pressure. Moreover, the unique transcriptional and replication dynamics of ecDNA with linking the uneven segregation during cell division, create a significant environment for the understanding of genetic diversity and adaptive evolution in tumors. In clinics the ecDNA holds significant potential as a biomarker for cancer, diagnosis, treatment, therapeutic monitoring and progenies. The higher level of ecDNA correlates with poor clinical outcomes and resistance to therapies, emphasizing its prognostic value. The current therapeutic techniques targeting ecDNA specific vulnerabilities, such as disrupting replication stress pathways or silencing the transcriptional activity, represents promising ways for cancer treatment This review also highlights the potential of circulating ecDNA in liquid biopsies as a non-invasive diagnostic and monitoring tool. Despite these advances, challenges such as standardizing detection methods and understanding ecDNA diverse roles across cancer types remain. Addressing these gaps will unlock new opportunities in precision oncology, making ecDNA a cornerstone of future cancer diagnostics and therapeutics. Bangladesh J Medicine 2025; 36(2): 82-91